Analysis of Deck Type Bridge Considering Vehicular Loading Using Analysis Tool STAAD.PRO - Soni, Deepak; Sathbhaiya, Rahul (International Journal of Scientific Research in Civil Engineering, 2020)
Bridge is an important structure required for the transportation network. Now a day with the fast innovation in technology the conventional bridges have been replaced by the cost-effective structured system. For analysis and design of these bridges the most efficient methods are available. Different methods which can be used for analysis and design are AASHTO, Finite element method, Grillage and Finite strip method. In this study Deck type bridge is analyzed considering UHPC concrete and NaOH treated concrete for vehicular load as per I.R.C. specifications using analysis tool Staad.pro and Beava. Here it is observed that utilizing UHPC concrete results in economic structure with stability and minimum observation of forces, displacement, moment and cost.
Keywords: Bridge; Deck; IRC; Stresses; Staad.pro; Analysis; Structure; Forces; Deflection